Mixed Method Research on Football Coaches’ Competitive Behavior - José Rodrigues; José Rodrigues; Filipe Rodrigues; Filipe Rodrigues; Rui Resende; Rui Resende; Mário Espada; Mário Espada; Fernando Santos; Fernando Santos (Frontiers in Psychology, 2021)
ObjectiveThe purpose of this study was to present the reliability of three validated measures, namely the System of Analysis of Instruction in Competition, the Questionnaire on Coach Instructional Behavior Expectations, and the Questionnaire on Coach Instructional Behavior Perception that could be used in a mix-method approach.MethodsThree instruments underwent a robust process of construct and reliability analysis. Inter− and intra-observer reliability was tested for the observational instrument using Cohen’s k-agreement measure. Reliability values above 0.85 were considered as a good agreement between and within observers. To verify the internal consistency of the questionnaires, the correlation coefficients were considered.ResultsThe results related to intra-observer and inter-observer reliability showed that intra-observer reliability k-agreement values ranged between 0.912 and 1 for observer 1, and 0.82 and 1 for observer 2. For inter-observer reliability, k-agreement values ranged between 0.885 and 1 between observers. Thus, values for reliability are above acceptable. The correlation coefficient values recorded for the questionnaires on instruction expectations in the competitive moment were above 0.82 and significant (p < 0.05), and for the questionnaire on instruction perception in competition above 0.88 and significant (p < 0.05). The pilot study showed some divergent results across expectations, behavior during competition, and perception about the instruction behavior.ConclusionThe observational system and the expectations and perceptions questionnaires, used in a complementary way, can be considered as a mix-method approach for studies aiming to examine coaches’ competitive behavior.